Antiproliferative Effects of Zinc-Citrate Compound on Hormone Refractory Prostate Cancer - Hong, Sung Hoo; Choi, Yong Sun; Cho, Hyuk Jin; Lee, Ji Youl; Kim, Joon Chul; Hwang, Tae Kon; Kim, Sae Woong (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: To investigate the antiproliferative effects of zinc-citrate compound on hormone refractory prostate cancer (HRPC). Methods: HRPC cell line (DU145) and normal prostate cell line (RWPE-1) were treated with zinc, citrate and zinc-citrate compound at different time intervals and concentrations to investigate the effect of zinc-citrate compound. Mitochondrial (m)-aconitase activity was determined using aconitase assay. DNA laddering analysis was performed to investigate apoptosis of DU145 cells. Molecular mechanism of apoptosis was investigated by Western blot analysis of P53, P21waf1, Bcl-2, Bcl-xL and Bax, and also caspase-3 activity analysis. Results: Treatment with zinc-citrate compound resulted in a time- and dose-dependent decrease in cell number of DU145 cells in comparison with RWPE-1. M-aconitase activity was significantly decreased. DNA laddering analysis indicated apoptosis of DU145 cells. Zinc-citrate compound increased the expression of P21waf1 and P53, and reduced the expression of Bcl-2 and Bcl-xL proteins but induced the expression of Bax protein. Zinc-citrate compound induced apoptosis of DU145 cells by activation of the caspase-3 pathway. Conclusion: Zinc-citrate compound can induce apoptotic cell death in DU145, by caspase-3 activation through up-regulation of apoptotic proteins and down-regulation of antiapoptotic proteins.